Reinterpretasi Profitabilitas sebagai Sinyal Financial Distress: Peran Faktor Makroekonomi pada Perusahaan Sektor Keuangan Indonesia - Najmi Aziza; Novita Weningtyas Respati (Owner : Riset dan Jurnal Akuntansi, 2026)
Financial distress is the first signal before a company goes bankrupt. This research is very important because it was conducted in the 2019-2023 period, which is the transition period from a pandemic crisis to an economic recovery full of uncertainty (crisis context). Although there is a lot of research on this topic, there is still a gap on whether traditional economic indicators still accurately predict risks in the financial sector when the world is in turmoil. This study examines the influence of exchange rates, inflation, and profitability on financial distress (Altman Z-Score) in 11 financial sector companies on the Indonesia Stock Exchange. The results of the study show an unusual finding: exchange rates, inflation, and even profitability have no effect on financial distress. This indicates an anomaly, where indicators that are usually very decisive do not become a direct threat to the financial sector during this period. These results show that the financial sector has strong resilience thanks to strict regulatory oversight. For investors and managers, these findings provide a lesson that in a crisis situation, profitability alone is not enough to assess risk, a deeper analysis of the company's internal policies and regulatory compliance is needed.